Equity valuation of Continental AG - Castro, Nuno Miguel Macias de (2018)
The aim of this dissertation is to evaluate Continental AG and estimate a fair target price for its shares. Continental is a German automotive tier one supplier that operates globally through its Automotive and Rubber Groups. The literature review presents the various valuation methods that can be used to evaluate a firm and the advantages and disadvantages of each one. After analyzing Continental’s financials, it was decided that the most appropriated methods for its valuation were the Discounted Cash Flow using the Weighted Average Cost of Capital and the Relative Valuation by applying a Sum of the Parts method. In order to support the forecasts used for the valuation it was made an analysis about the world economy and the automotive industry which are two factors that influence Continental’s future performance. After the forecasts were made, the DCF method indicated a valuation of €241 per share, and the Relative Valuation a lower share price of €224 due to the fact that this method doesn’t capture the higher profitability of Continental’s Rubber Group in comparison with its peers and consequently undervalues the firm. For this reason the target price is only based on the DCF valuation. Lastly, it was made a comparison with an Investment Bank report about Continental, in which it is discussed the main differences in the forecasts made.